2012
DOI: 10.1029/2011gl050554
|View full text |Cite
|
Sign up to set email alerts
|

Slow rupture of frictional interfaces

Abstract: [1] The failure of frictional interfaces and the spatiotemporal structures that accompany it are central to a wide range of geophysical, physical and engineering systems. Recent geophysical and laboratory observations indicated that interfacial failure can be mediated by slow slip rupture phenomena which are distinct from ordinary, earthquakelike, fast rupture. These discoveries have influenced the way we think about frictional motion, yet the nature and properties of slow rupture are not completely understood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
109
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 25 publications
6
109
0
Order By: Relevance
“…In particular, frictional instabilities that mark the transition from creep-like motion to rapid slip and a variety of emerging rupture fronts have been observed. Quantitatively understanding these complex dynamics and their dependence on geometry, external forcing, system's history and constitutive behavior of the frictional interface remains an important challenge.In this Letter we present a theoretical analysis of a simple, yet realistic, quasi-1D rate-and-state model [34,35] in which friction is velocity-weakening at low slip velocities and crosses over to velocity-strengthening at higher velocities [36][37][38]. Using combined analytic and numeric tools we elucidate the physics of a sequence of instabilities at a frictional interface.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, frictional instabilities that mark the transition from creep-like motion to rapid slip and a variety of emerging rupture fronts have been observed. Quantitatively understanding these complex dynamics and their dependence on geometry, external forcing, system's history and constitutive behavior of the frictional interface remains an important challenge.In this Letter we present a theoretical analysis of a simple, yet realistic, quasi-1D rate-and-state model [34,35] in which friction is velocity-weakening at low slip velocities and crosses over to velocity-strengthening at higher velocities [36][37][38]. Using combined analytic and numeric tools we elucidate the physics of a sequence of instabilities at a frictional interface.…”
mentioning
confidence: 99%
“…In this Letter we present a theoretical analysis of a simple, yet realistic, quasi-1D rate-and-state model [34,35] in which friction is velocity-weakening at low slip velocities and crosses over to velocity-strengthening at higher velocities [36][37][38]. Using combined analytic and numeric tools we elucidate the physics of a sequence of instabilities at a frictional interface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent numerical and experimental studies have shown that, depending on friction and stress conditions, slow rupture modes occur either as isolated events or in conjunction with much faster modes (Rubinstein et al 2004;Ben-David et al 2010a;Nielsen et al 2010;Kaneko and Ampuero 2011;Bar Sinai et al 2012). However, previous laboratory experiments on rocks have focused on stick-slip events for bare surfaces of granite and dunite under a relatively narrow range of normal stress conditions (equivalent to less than approximately 10 MPa) (e.g., Johnson and Scholz 1976;Okubo and Dieterich 1984;Kato et al 1992;Ohnaka and Shen 1999), although the values of duration and propagation velocity for the SSEs (Gao et al 2012) may be influenced by variations in effective normal stress on the plate interface.…”
Section: Introductionmentioning
confidence: 99%